Agony Hill : a mystery - Taylor, Sarah Stewart (Franklin Warren, 2024)
"Set in rural Vermont in the volatile 1960s, Agony Hill is the first novel in a new historical series full of vivid New England atmosphere and the deeply drawn characters that are Sarah Stewart Taylor's trademark. In the hot summer of 1965, Bostonian Franklin Warren arrives in Bethany, Vermont, to take a position as a detective with the state police. Warren's new home is on the verge of monumental change; the interstates under construction will bring new people, new opportunities, and new problems to Vermont, and the Cold War and protests against the war in Vietnam have finally reached the dirt roads and rolling pastures of Bethany. Warren has barely unpacked when he's called up to a remote farm on Agony Hill. Former New Yorker and Back-to-the-Lander Hugh Weber seems to have set fire to his barn and himself, with the door barred from the inside, but things aren't adding up for Warren. The people of Bethany - from Weber's enigmatic wife to Warren's neighbor, widow and amateur detective Alice Bellows - clearly have secrets they'd like to keep, but Warren can't tell if the truth about Weber's death is one of them. As he gets to know his new home and grapples with the tragedy that brought him there, Warren is drawn to the people and traditions of small town Vermont, even as he finds darkness amidst the beauty"--